(untitled) (Education in the 21st Century, 2023)
For centuries, the people’s biophilosophy, value system, and educational ideas have been concentrated in Armenian traditions, folk works, emphasizing the issues of national consciousness, human dignity, and the formation of a God-pleasing image of a person. For hundreds of years, regardless of the change in the goals of education in different historical and cultural periods, regardless of the historical and social processes in the given period, regardless of the ruling ideologies, regardless of the different models and paradigms of education, the same questions have always been at the basis: who should be educated, how to educate and what values to form? In all cases, the task of the society was the upbringing of such a person who would be the bearer and transmitter of national, spiritual and moral values. Catholicos of All Armenians, the greatest thinker of the 20th century, devotee of the motherland and embodiment of patriotism, Karegin I, addressed these issues. The Catholicos, the son of the people living in the geographic and political crossroads, discussed and advocated the idea of the motherland everywhere: on international platforms, at meetings of the clergy, in mass sermons, public speeches, dozens of articles and works.